Profile of Prescribing Chemotherapy Regimens for High-Risk Acute Leukemia in Children : Profil Peresepan Regimen Kemoterapi Leukemia Akut Risiko Tinggi Pada Anak - Ninik Mas Ulfa; Eka Sari (Akademi Farmasi Surabaya, 2023)
Cancer is one of the non-communicable diseases but is a health problem in the world, including in Indonesia. The results of the 2018 Basic Health Research showed that the prevalence of cancer rose from 1.4% in 2013 to 1.8% in 2018. Acute Lymphoblastic Leukemia (ALL) is a malignant disease characterized by progressive infiltration of immature lymphoid cells in the bone marrow and lymphatic organs. , with leukocyte cells proliferating irregularly and uncontrollably. This study aims to analyze the descriptive profile of prescribing high-risk ALL chemotherapy regimens in children at a hospital in East Surabaya. This study was conducted on inpatients, chemotherapy regimens using the 2018 ALL National Protocol. The protocol consists of 4 phases of chemotherapy, namely the induction, consolidation, intensification and maintenance phases. The results of the study from the drug administration record data, there were 143 pediatric patients with a diagnosis of ALL. high risk from the period July to August 2022. The most widely used drug classification is the glucocorticoid group with use in the induction phase 38,17%, intensification 43,2%, and maintenance 50%. Dexamethasone was the most used generic name 38,17% was used in the induction phase and 43,2% for the intensification phase. The use of ALL chemotherapy doses is Dexamethasone with doses based on the age of the child, the most being 1 mg (97,62%) and 12 mg (88,10%).